1985
DOI: 10.1111/j.1365-2125.1985.tb05106.x
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of doxepin and N‐desmethyldoxepin in human milk.

Abstract: Doxepin and N‐desmethyldoxepin concentrations in plasma and breast milk from a lactating mother and in plasma from her infant were measured during an 8 week period using high performance liquid chromatography. Plasma concentrations ranged from 35‐68 microgram l‐1 for doxepin and 65‐131 microgram l‐1 for N‐desmethyldoxepin. Mean pre‐feed milk/plasma ratios were 1.08 and 1.02 for doxepin and N‐desmethyldoxepin respectively and increased to 1.66 and 1.53 at the post‐feed samples. Only N‐desmethyldoxepin (15 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Two single case studies have been published of mothers receiving daily doses of doxepin, 75 mg (Matheson et al, 1985) and 150 mg (Kemp et al, 1985). Maternal plasma concentrations of doxepin and desmethyldoxepin in the first subject (Matheson et al, 1985) went up to maxima of 15 and 57 nglml and milkplasma ratios were below 0.9 and 0.2 respectively.…”
Section: Doxepinmentioning
confidence: 95%
See 1 more Smart Citation
“…Two single case studies have been published of mothers receiving daily doses of doxepin, 75 mg (Matheson et al, 1985) and 150 mg (Kemp et al, 1985). Maternal plasma concentrations of doxepin and desmethyldoxepin in the first subject (Matheson et al, 1985) went up to maxima of 15 and 57 nglml and milkplasma ratios were below 0.9 and 0.2 respectively.…”
Section: Doxepinmentioning
confidence: 95%
“…The infant was observed to be pale, sweaty, drowsy and with depressed respiration, symptoms which improved following cessation of breast feeding. The mother investigated by Kemp et al (1985) was taking 150 mglday of doxepin and her plasma concentrations of the drug and its metabolite were 46 and 90 ng/ml respectively. Milk plasma ratios were about 1.1 for fore-milk and over 1.5 for hind-milk and despite the fact the infant was ingesting much bigger 'doses', neither the drug nor its metabolite were detectable in its plasma (sensitivity 5 and 15 ng/ml respectively).…”
Section: Doxepinmentioning
confidence: 99%
“…[15] On the other hand, no adverse effects were noted for the breastfed infant of a mother receiving doxepin. [13] These 2 case reports illustrate the variability in response for individuals and the unreliability of making general recommendations from a limited database. Even where a drug appears to be well tolerated, vigilance is required at the beginning of treatment or when the dose is increased.…”
Section: Adverse Effects On Infants From Exposure To Antidepressant Dmentioning
confidence: 97%
“…The findings have generally indicated that, despite adequate maternal serum concentrations, either the parent drug and/or its metabolites were not detected in the infant's serum, [3][4][5][6][7][8][9][10][11][12] or very low concentrations were observed. [13][14][15][16][17][18][19][20][21][22][23][24][25] Studies have measured maternal plasma and breast milk concentrations of antidepressants, demonstrating that infants would be receiving a dose, albeit low, of parent drug and its metabolites. [3,4,6,7,9,12,13,[15][16][17][19][20][21][22][23][25][26][27][28][29][30][31][32][33][34][35]…”
mentioning
confidence: 99%
See 1 more Smart Citation